Tioconazole and Chloroquine Act Synergistically to Combat Doxorubicin-Induced Toxicity via Inactivation of PI3K/AKT/mTOR Signaling Mediated ROS-Dependent Apoptosis and Autophagic Flux Inhibition in MCF-7 Breast Cancer Cells - Afnan H. El-Gowily; Samah A. Loutfy; Ehab M. M. Ali; Tarek M. Mohamed; Mohammed A. Mansour (MDPI AG, 2021)
Cancer is a complex devastating disease with enormous treatment challenges, including chemo- and radiotherapeutic resistance. Combination therapy demonstrated a promising strategy to target hard-to-treat cancers and sensitize cancer cells to conventional anti-cancer drugs such as doxorubicin. This study aimed to establish molecular profiling and therapeutic efficacy assessment of chloroquine and/or tioconazole (TIC) combination with doxorubicin (DOX) as anew combination model in MCF-7 breast cancer. The drugs are tested against apoptotic/autophagic pathways and related redox status. Molecular docking revealed that chloroquine (CQ) and TIC could be potential PI3K and ATG4B pathway inhibitors. Combination therapy significantly inhibited cancer cell viability, PI3K/AkT/mTOR pathway, and tumor-supporting autophagic flux, however, induced apoptotic pathways and altered nuclear genotoxic feature. Our data revealed that the combination cocktail therapy markedly inhibited tumor proliferation marker (KI-67) and cell growth, along with the accumulation of autophagosomes and elevation of LC3-II and p62 levels indicated autophagic flux blockage and increased apoptosis. Additionally, CQ and/or TIC combination therapy with DOX exerts its activity on the redox balance of cancer cells mediated ROS-dependent apoptosis induction achieved by GPX3 suppression. Besides, Autophagy inhibition causes moderately upregulation in ATGs 5,7 redundant proteins strengthened combinations induced apoptosis, whereas inhibition of PI3K/AKT/mTOR pathway with Beclin-1 upregulation leading to cytodestructive autophagy with overcome drug resistance effectively in curing cancer. Notably, the tumor growth inhibition and various antioxidant effects were observed in vivo. These results suggest CQ and/or TIC combination with DOX could act as effective cocktail therapy targeting autophagy and PI3K/AKT/mTOR pathways in MCF-7 breast cancer cells and hence, sensitizes cancer cells to doxorubicin treatment and combat its toxicity.